Neoaortic Bicuspid Valve Replacement in Patient After Arterial Switch Operation to Correct Dextro-Transposition of the Great Arteries - V. S. Selyaev; A. V. Redkoborody; N. V. Rubtsov; O. Yu. Kornoukhov; S. S. Niyazov; N. M. Bikbova; R. Sh. Muslimov (Неотложная медицинская помощь)
INTRODUCTION Transposition of the great arteries is the second most common cyanotic congenital heart defect after tetralogy of Fallot. The arterial switch procedure (А. Jatene, 1975) is the surgical treatment of choice. Neoaortic root dilatation and valve regurgitation are quite common among the patients who underwent surgery for transposition of the great arteries. However, there are a lot of conflicting data about their direct connection.CLINICAL CASE This article describes surgical repair of neoaortic bicuspid valve regurgitation, by it successful implantation, in an  18-year-old  patient  after arterial switch operation for transposition of the great arteries in the neonatal period.CONCLUSION Neoaortic valve insufficiency can develop primarily as well as secondary to neoaortic root dilatation, however, the questions about valve repair or aortic root replacement with or without neoaortic valve implantation remains debatable. At this stage, decision making is based only on unsystematic clinical experience, surgeon’s intuition, the basics of anatomy and pathophysiology, as well as close interaction of “pediatric” and “adult” cardiac surgeons.